2017
DOI: 10.1016/j.proci.2016.06.126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure waves on the stability of flames propagating in tubes

Abstract: Numerical simulations were performed to study the effects of pressure waves on the evolution and stability of flames propagating in tubes. The model is the fully compressible reactive Navier-Stokes equations coupled to a calibrated one-step chemical-diffusive model for combustion in a stoichiometric hydrogen-air mixture. The numerical solution method is high order in space and time, and adaptive mesh refinement provides adequate resolution of flames, boundary layers, acoustic waves, and all of their interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In confined regions, detonations may take place after flame acceleration and DDT, propagating with a velocity below the CJ detonation velocity. The velocity deficit can be credited to the heat and momentum losses or detonation front curve [46,82,85]. As suggested by Lee [75], the deficits are seldom larger than 15% when the detonation fails in smooth tubes.…”
Section: Detonationmentioning
confidence: 95%
See 2 more Smart Citations
“…In confined regions, detonations may take place after flame acceleration and DDT, propagating with a velocity below the CJ detonation velocity. The velocity deficit can be credited to the heat and momentum losses or detonation front curve [46,82,85]. As suggested by Lee [75], the deficits are seldom larger than 15% when the detonation fails in smooth tubes.…”
Section: Detonationmentioning
confidence: 95%
“…After a weak ignition, four flame morphologies in the early stages can be distinguished in pipes/tubes [43]: (1) hemispherical flame; (2) finger-shaped flame; (3) skirt of flame front touching the sidewalls and (4) tulip flame. Xiao et al [44] found a new fifth morphology, "distorted tulip" flame, which is characterized by Rayleigh-Taylor instability driven by pressure waves [45,46]. The sketch of these morphologies is shown in Figure 5.…”
Section: Dynamics Of Flame Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Clanet 23 studied the tulip flame phenomenon in a half-open tube and noted that the formation of the tulip flame is a manifestation of the Taylor instability driven by the deceleration of the flame tip. In recent works, [24][25][26] experimental and numerical investigations were performed to study a new flame shape, called "distorted tulip" flame (DTF), which appears after a classical tulip flame is formed. In these works, Xiao et al 25 suggested that the formation of a DTF is the result of Rayleigh-Taylor instability (RTI) driven by pressure waves generated by contact of the flame front with the sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…In recent works, [24][25][26] experimental and numerical investigations were performed to study a new flame shape, called "distorted tulip" flame (DTF), which appears after a classical tulip flame is formed. In these works, Xiao et al 25 suggested that the formation of a DTF is the result of Rayleigh-Taylor instability (RTI) driven by pressure waves generated by contact of the flame front with the sidewalls. Meanwhile, shock-flame bubble interactions in terms of Richtmyer-Meshkov Instability (RMI) are also extensively investigated.…”
Section: Introductionmentioning
confidence: 99%